A Novel In Vivo Method Using Caenorhabditis elegans to Evaluate α-Glucosidase Inhibition by Natural Products for Type 2 Diabetes Treatment - María Pilar de Torre; José Luis Vizmanos; Rita Yolanda Cavero; María Isabel Calvo (Pharmaceuticals)
Background: Non-insulin-dependent diabetes mellitus, or type 2 diabetes, is one of the diseases of greatest concern worldwide, and research into natural compounds that are capable of regulating glycemia and insulin resistance is therefore gaining importance. In the preclinical stages, Caenorhabditis elegans is considered a promising in vivo model for research into this disease. Most studies have been carried out using daf-2 mutant strains and observing changes in their phenotype rather than directly measuring the effects within the worms. Methods: We evaluated the in vitro α-glucosidase inhibition of two oral formulations of Origanum vulgare before and after a simulated gastrointestinal digestion process. After confirming this activity, we developed a method to measure α-glucosidase inhibition in vivo in the C. elegans wild-type strain. Results: The crude extract showed a similar IC50 value to that of acarbose (positive control), before and after gastrointestinal digestion. Formulation 1 also showed no differences with the positive control after digestion (111.86 ± 1.26 vs. 110.10 ± 1.00 µL/mL; p = 0.282). However, formulation 2 showed a higher hypoglycemic activity (59.55 ± 0.85 µL/mL; p < 0.05). The IC50 values obtained in the in vivo assays showed results that correlated well with the in vitro results, so the proposed new method of direct quantification of the in vivo activity seems suitable for directly quantifying the effects of this inhibition without the need to measure changes in the phenotype. Conclusion: A novel, simple and reliable method has been developed to directly determine pharmacological activities in an in vivo model of wild-type C. elegans. This allows the hypoglycemic activity to be directly attributed to in vivo treatment without quantifying phenotypic changes in mutant strains that may arise from other effects, opening the door to a simple analysis of in vivo pharmacological activities.